Increased nuchal translucency before 11 weeks of gestation: Reason for referral?. (8th October 2021) - Lugthart, Malou A.; Bet, Bo B.; Elsman, Fleur; van de Kamp, Karline; de Bakker, Bernadette S.; Linskens, Ingeborg H.; van Maarle, Merel C.; van Leeuwen, Elisabeth; Pajkrt, Eva
Abstract: Objectives: In this era of non‐invasive‐prenatal testing (NIPT), when dating scans are usually performed around 10 weeks of gestation, an increased NT before the official established timeframe (CRL between 45 and 84 mm) may be encountered. Information on management of these pregnancies is limited. Therefore, we evaluated the relationship between an early increased NT and adverse pregnancy outcome. Secondary, we evaluated the rate of chromosomal anomalies that might have been missed in first trimester should solely NIPT be performed as first‐tier test, and the rate of adverse pregnancy outcome if NT normalizes before 14 weeks. Methods: We performed a retrospective cohort study that included all pregnancies between January 1, 2007 and June 1, 2020 in Amsterdam UMC locations AMC and VUmc. We included fetuses with a crown‐rump length (CRL) < 45 mm (∼11 weeks) and a nuchal translucency (NT) measurement ≥2.5 mm. Fetuses referred with an early increased NT and a major fetal anomaly at the dating scan were excluded, as were cases of parents with a family history of monogenetic disease(s) or recognized carriers of a balanced translocation. Results: We included 120 fetuses of which 66.7% (80/120) had an adverse pregnancy outcome. Congenital anomalies were present in 56.7% (68/120), 45.8% (55/120) had a chromosomal anomaly. The prevalence of congenital anomalies was 30.3% in fetuses with NT 2.5–3.4 mm compared to 66.7% with NT ≥ 3.5 mm ( p < 0.001). 16.7% (20/120) had a chromosomal anomaly that might have been missed by conventional NIPT in first trimester. We found an adverse pregnancy outcome of 24% in the group with a normalized NT compared to 78.1% in the group with a persistently increased NT ( p < 0.001). Conclusion: An early increased NT should make the sonographer alert. In this selected cohort, an early increased NT was associated with a high probability of having an adverse pregnancy outcome. Regardless of CRL, we deem that an early increased NT ≥ 3.5 mm warrants referral to a Fetal Medicine Unit for an extensive work‐up. NT normalization seems favorable, but a prospective study should define the appropriate work‐up for NT in the lower range (2.5–3.4 mm). Key points: What's already known about this topic? Increased nuchal translucency (NT) is an indisputable marker for chromosomal anomalies and adverse pregnancy outcomes. The current age to perform a NT measurement is between 11 and 14 weeks of gestation, corresponding with a crown rump length (CRL) of 45–84 mm. What does this study add? An increased NT with CRL <45 mm, and thus before the official timeframe, could be found when a dating scan is performed around 10 weeks of gestation preceding non‐invasive‐prenatal testing (NIPT). This early increased NT, with NT ≥ 2.5 mm and CRL <45 mm should make sonographers alert. Regardless of CRL, an early increased NT ≥ 3.5 mm warrants referral to a Fetal Medicine Unit for an extensive work‐up. In cases with early increased NT 2.5–3.4 mm, the additional value of a systematic follow‐up in a Fetal Medicine Unit should be further explored in a prospective study.